La Palmada en la Frente (1970): Political Cartoons, the Global Sixties, and Popular Culture in Chile. - Hermosilla, Matías (Studies in Latin American Popular Culture, 2020)
This article examines the case of La Palmada en la Frente (1970), a one-issue political cartoon magazine, drawn and written by cartoonist Lugoze and produced in the context of a scare campaign against the possible election of the socialist Salvador Allende (1969–1970). This ephemeral document belonged to a larger group of publications that used humor and cartoons as ideological weapons. An extensive examination of this source allows a recast of the relationship between popular culture and politics in the Chilean experience of the global sixties. This essay argues that political cartoons work as a portal through which to understand behaviors, social problems, prejudices, fears, stereotypes, and myths that can enforce and challenge the study of Latin American popular culture and the sixties.